Effect of TiO2 on Melting and Crystallization Mechanism of Fused Magnesia - Xie, Xiang; Lu, Guimin; Du, Wei; Wang, Yinxiong; Yu, Jianguo (Asian Journal of Chemistry, 2015)
Fused magnesia was prepared by electric arc furnace melting method using high purity brine magnesia as raw material. The melting and crystallization mechanism of fused magnesia containing 0.15, 0.25 and 0.35 wt % TiO2 have been investigated. The bulk density, impurity content, crystal type and microstructure of product samples were characterized by Archimedes Method, ICP-AES, XRD, SEM, respectively. Results indicated that fused magnesia with purity of 99.472 wt %, bulk density of 3.569 g/cm3 and apparent porosity of 0.595 % could be obtained with addition of TiO2 less than 0.25 wt %. It can promote impurities diffusion, MgO crystallization and structural densification. However, excess TiO2 (> 0.35 wt %) over the solid solubility limit reacted with MgO to form magnesium titanate (Mg2TiO4), meanwhile the magnesia crystal was irregular and microstructure changed.